"Group-it": An Innovative Program for Scaling up Dissemination of Photovoltaic Panels - Florian Bürki; Joëlle Mastelic (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Virtual Conference, 10-12 September 2020, 2020)
With 3% of the electricity produced by solar panels according to the Swiss Federal Office for Energy, Switzerland is behind the plan regarding the use of solar energy. Acceptance and dissemination of existing technology are key. This paper describes a co-designed program supporting citizens in the process of installing photovoltaic panels. The method used is based on the Living Lab Integrative Process, a mixed-method combining surveys, qualitative interviews and focus groups. We first explore the main motivations and barriers of the citizen with and without the co-designed program. We collected more than 350 observations to describe the main barriers to actions. We then developed a focus group to co-design the program with the main stakeholders including professionals, researchers and citizen. The principal barriers are linked to a lack of transparency in information and economic reasons. The main motivational drivers are energy independence and desire for greening their lifestyle. Support for decision making and the profitability of the panels are identified drivers which help citizens to be involved in the process and increase their motivation and acceptance regarding the program.
Keywords: O32; O36; Q20; 330; sustainable consumption; citizen implication; renewable energy; Co-design; social innovation